PENGARUH KECERDASAN EMOSIONAL, KOMUNIKASI INTERPERSONAL, KOMITMEN ORGANISASI TERHADAP MANAJEMEN STRES KERJA - Dea Ayu Tri Wulandari; Susilawati (CV. ADIBA AISHA AMIRA, 2023)
Stress at work is not a new phenomenon. Effective work stress management enables employees to maintain self-control in the work environment so that problems that arise can be accepted as challenges and not threats. The results of the study prove that emotional intelligence and interpersonal communication have an influence on stress management. Meanwhile, organizational commitment has no significant effect on work stress management. Another finding is that interpersonal communication has a significant effect on organizational commitment. Namely, that the influence of interpersonal communication on organizational commitment is determined by how close and individual needs to maintain relationships with certain social groups/organizations. Meanwhile, organizational commitment has no significant effect on interpersonal communication. This is a consequence of life in an era of abundance of information, where individuals can choose forms of communication from traditional to electronic media communications to maintain self-commitment to the organization